The Tropical Cyclone Tracks and Formation over the Western Indian Ocean, And Impacts on the Iranian Southern Coasts - Mojtaba Zoljoodi (International Journal of Coastal and Offshore Engineering, 2019)
Cyclones are as one of the most dangerous meteorological phenomena of the tropical region that generate strong winds and heavy rainfall, impacting coastal regions. Behavior of tropical cyclone trajectories needs to be better understood in order to find predictable aspects of landfall potentially. This research aims to analyze the cyclone tracks statistically and then study of the associated meteorological effects of Gonu cyclone in June 2007 as an example. Using the cluster analysis (K-mean method) 5 principal clusters have been derived and spatial – temporal studies including the monthly variation of cyclone trajectories and their intensity and frequencies are performed. The 4th cluster indicated more spatial variability and expansion (4º-31ºN and 48.5º-78ºE). The second cluster showed the highest frequency with 349 events as well as the highest maximum intensity and standard deviation of 235.2km/h and 47.96km/h respectively. During 1-7 June 2007, the Gonu super cyclone traversed the Arabian Sea and reached the Iranian southern regions affecting the coastal infrastructures and communities. In this 7-day period the daily composite maps of different atmospheric levels showed that by intensifying of Gonu cyclone the axis of subtropical high pressures in the lower levels moved to the east and in the 500hp level they moved to the northward over the study region.